STATIN ADVERSE EFFECTS: MECHANISMS, DIAGNOSIS, PREVENTION AND MANAGEMENT - A. I. Dyadyk; T. E. Kugler; Y. V. Suliman; S. R. Zborovskyy; I. I. Zdykhovskaya (Архивъ внутренней медицины)
Statins are one of the most common lipid-lowering drugs in clinical practice. The purpose of this review was to systemize the most frequent statin adverse effects, including mechanisms, diagnosis, treatment and prevention. The frequency of statin-associated muscle symptoms is significantly higher in registries and observational studies than in randomized controlled trials. Diagnosis of muscle symptoms is difficult because it is subjective. The serum creatine kinase is often normal or slightly elevated. Association between statin use and the risk of new cases of diabetes mellitus was demonstrated in numerous studies. The drug interaction of statins, high dosage and concomitant diseases can lead to a persistent and clinically significant increase of hepatic enzymes. Basic glycemic tests, hepatic enzymes and serum creatine kinase have been necessary done before statin administration to identify patients with high risk of intolerance. The risk of hemorrhagic strokes after statin therapy is ambiguous due to randomized controlled trials. It is suggested that statins can inhibit cancerogenesis by inducing apoptosis or reducing cell growth, angiogenesis, and invasion. However, the results of preclinical and clinical studies are conflicting. The majority of the studies are observational or of retrospective nature. It is necessary to provide a larger prospective randomized placebo-controlled trials with a long follow-up. Any doctor should know the potential negative consequences of statins taking into account their expansion. Understanding the pharmacokinetics of statins is important for the safety of patients. Dosages, metabolism and risk factors of drug interactions should be considered to minimize statin adverse effects.